Heart failure patients’ experiences of self-care neglect: a content analysis - Parisa Sadat Bahrodi; Azade Safa; Neda Mirbagher Ajorpaz; Fatemeh Sadat Izadi Avanji (BMC Cardiovascular Disorders)
Abstract Background Heart failure is a chronic and common disorder worldwide. Patients with heart failure need self-care behaviors to manage their condition. Despite the importance of self-care in positive health outcomes, many patients with heart failure neglect their self-care behaviors. Therefore, the present study was conducted to explain heart failure patients’ experiences of self-care neglect. Methods This qualitative study was conducted using conventional content analysis method. Participants included 15 patients with heart failure. Data were collected through semi-structured interviews and using purposive sampling method. Sampling continued until data saturation was reached. Data analysis was performed concurrently with data collection. Lincoln and Guba’s four criteria were used to ensure the trustworthiness of the data. Data management was performed using MAXQDA version 24 software. Results The results were presented in the form of four main categories and 10 subcategories. In analyzing the data of the study, four main categories emerged in the participants’ experiences: “false cultural beliefs in self-care”, “weakening of mental-psychological power”, “synergy of physical problems”, and “inappropriate support”. Conclusion The patients in their experiences of neglect in self-care pointed to false cultural beliefs in self-care, weakening of mental-psychological power, synergy of physical problems, and inappropriate support. Knowing the factors that influence self-care neglect and preventing their occurrence can improve self-care skills and prevent neglect-related side effects in patients with heart failure. Healthcare providers can help improve the health of these patients by developing interventions to mitigate these factors. It is suggested that future research be designed in the form of an intervention to reduce the effect of each of these factors. Trial registration This is a qualitative study and has not been registered in Iranian Registry of Clinical Trials.